Killer yeasts used as starter cultures to modulate the behavior of potential spoilage non-Saccharomyces yeasts during Malbec wine fermentation - Fernandez de Ullivarri, Miguel (2023)
east contamination is an important problem that affects wine production worldwide. In the present work, fermentative and biocontrol properties under winemaking conditions of the two killer strains, Saccharomyces cerevisiae Cf8 and Wickerhamomyces anomalus Cf20, were evaluated. S. cerevisiae Cf8 and its combination with W. anomalus Cf20 were able to effectively control the growth of Meyerozyma guilliermondii Cd6 at low SO2 concentrations during Malbec must fermentation. Although the killer strain Cf8 alone exerted lower inhibitory activity, it modulated the growth of the strain Cd6, which positively influenced on wine aroma and complexity without being detrimental to product quality. Malbec wine produced by mixed culture Cf8 and Cd6 was the preferred one by the judges in the sensory analysis. To our knowledge, this is the first study made on red wines produced with indigenous killer yeasts from the Northwest Region of Argentina, as well as the first report of the modulation of potential spoilage yeasts into positive starters using killer yeasts in wine production. These results suggest that killer yeasts could be utilized as starter cultures to produce regional wines using low concentrations of SO2.